2018
DOI: 10.1111/joop.12206
|View full text |Cite
|
Sign up to set email alerts
|

How can mindfulness be promoted? Workload and recovery experiences as antecedents of daily fluctuations in mindfulness

Abstract: While previous work on mindfulness has focused predominantly on the benefits of mindfulness and of mindfulness interventions, the present article addresses the question of how natural experiences of mindfulness can be promoted in the context of work. Accordingly, this article sheds light on day‐to‐day fluctuations in workload and recovery experiences (psychological detachment and sleep quality) as antecedents of state mindfulness. Furthermore, this study extends extant research that has documented beneficial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 73 publications
4
73
0
Order By: Relevance
“…Finally, previous research has demonstrated how feedback loops and gain spirals might contribute to the positive effects of MBPs. 92 93 More recently, a study by Hülsheger et al 94 on state mindfulness in working populations showed how previous day recovery experiences benefitted mindfulness and subsequent recovery experience (gain spiral), whereas workload hampered the experience of mindfulness as well as subsequent recovery experience (loss spiral). Findings from our review support these observations by proposing that resource gains and losses in workplace MBPs may have to be seen in the context of resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous research has demonstrated how feedback loops and gain spirals might contribute to the positive effects of MBPs. 92 93 More recently, a study by Hülsheger et al 94 on state mindfulness in working populations showed how previous day recovery experiences benefitted mindfulness and subsequent recovery experience (gain spiral), whereas workload hampered the experience of mindfulness as well as subsequent recovery experience (loss spiral). Findings from our review support these observations by proposing that resource gains and losses in workplace MBPs may have to be seen in the context of resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date it is not so clear how job and personal resources can interact in predicting job burnout, and future research should invest more interest about the role exerted from mindfulness. In this vein, future studies could focus on the booster effect that the interaction between job resources and personal resources may have on work engagement [63].…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, results of the present study could be further analyzed within health promotion intervention aimed at sustain teachers’ wellbeing through MBI interventions. For example, future studies can improve the extant knowledge about the effect of mindfulness training [63] on mindfulness state, using diary studies to integrate the JD-R assumption about the potential mediating role of stress appraisal and the way by which teachers value their work as full of meaning.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mindfulness has been examined as a trait in the majority of published empirical studies within and outside the organizational sciences, as pointed out by a number of researchers (Blanke, Riediger, & Brose, 2018;Hülsheger, Walkowiak, & Thommes, 2018;Olafsen, 2017;Tuckey, Sonnentag, & Bryan, 2018). Yet mindfulness is inherently a state experienced during specific moments in time (such as particular epochs of work activity).…”
Section: Problem Solving Confidence and Affect As Mechanisms Linkinmentioning
confidence: 99%
“…A number of characteristics of mindfulness can impact on affect experienced in the workplace. In particular, mindful employees are able to attend to the present moment in a non-judgemental way, evaluate stressful events in an objective manner separate from one's self as well as maintain an open and accepting awareness of one's thoughts and feelings (Hülsheger et al, 2013(Hülsheger et al, , 2018Shapiro et al, 2006;Slutsky, Rahl, Lindsay, & Creswell, 2017). Such characteristics are likely to improve emotional processing and regulation, particularly in response to difficult interactions and in the face of demanding situations.…”
Section: Affective Pathwaymentioning
confidence: 99%